Mobile Payment Technology Adoption in SME Owners in India – An Empirical Study - Navena Nesa Kumari, J.; Joe Arun, C.; Irudaya Veni Mary, A. (Indian Journal of Finance, 2021)
This paper focused on mobile payment technology adoption among SME owners in Kanchipuram district in Tamil Nadu, India. It attempted to explore the factors that affected the adoption of mobile payment technology and the intention to use it. The paper sought to identify the issues faced by the SME owners while adopting mobile payment technology for their personal and business transactions. The data were collected using an interview schedule, and the sample comprised of 100 SME owners in the selected rural areas of Kanchipuram district. The primary data were analyzed using regression and correlation analysis. The findings revealed that the mobile payment usage enabled the SME owners to accomplish their work rapidly. The study observed that the factors such as complexity, cost, trust, and security issues derived from perceived ease of use and perceived usefulness had a positive impact on the adoption of mobile payment technology. The study was a novel attempt to empirically examine the factors affecting the mobile payment technology adoption in rural India. The study will be useful for the service providers to advance the critical understanding on how rural consumers can improve their technology adoption and optimize their business opportunities in the emerging market of rural India.